Analisis Fase Mitosis pada Akar Bawang Merah (Allium cepa) yang Direndam dalam Air Beras, Air Kelapa Muda, dan Air Biasa - Damai Agatha Tarihoran; Marsedina Berutu; Winda Resta Laoli; Putu Azkia Shafrina; Larasati Arum Utami (Mataram University, 2026)
Mitosis cell division is an important process in plant growth and occurs actively in meristematic tissues, one of which is the root tip of shallots (Allium cepa). Mitotic activity can be influenced by the growing medium used, especially media containing nutrients and growth regulators. This study aimed to examine the process of mitotic cell division in shallot root tips soaked in three different media, namely plain water, rice washing water, and young coconut water. The research was conducted using an experimental method with a descriptive approach. Shallots were soaked for approximately 48 hours until roots were formed, then the root tips were prepared using the squash method and observed under a light microscope. The observed parameters included the stages of mitosis and root growth. The results showed that the plain water medium only exhibited prophase and telophase stages with low mitotic activity. The rice washing water medium showed telophase and cytokinesis stages with moderate mitotic activity. Meanwhile, the young coconut water medium exhibited more complete mitotic stages, namely prophase, telophase, and cytokinesis, and produced the most optimal root growth. These findings indicate that the type of soaking medium affects mitotic activity in shallot roots, with young coconut water being the most effective medium in supporting cell division.